Individual differences in main idea identification and text summarization in EFL reading comprehension: an exploratory study - Prebianca, Gicele Vergine Vieira (Revista Leitura, 2019)
This exploratory small-scale study investigates EFL learners' ability to read in a foreign ianguage, particularly their main idea identification and text summarization skills as products of their reading comprehension processes. Four pre-intermediate students, classified as good and poor language learners, participated in the study. Learners were asked to read a text; select its main idea(s) based on a list of options provided and then, write a summary of the main points addressed in the text. Results suggest that poor and good language learners did differ in what they consider important in a text and that level of proficiency appears to influence learners' ability to select and summarize important information. DOI: 10.28998/0103-6858.2007v1n39p199-222